Impacts of neglecting African Traditional Environmental Conservation Practices and education on the environment: A Case of the Maasai People of Narok County, Kenya - Jackson Morompi1*, Walingo Mary2, Osano Aloys3 Bulitia Godrick4 and Bakari Chaka3* (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2022)
Neglecting African traditional practiceshas contributed to numerous environmental problems inKenya. These include reduced arable land, forests and habitat destruction, loss of biodiversity,pollution and change in weather and climate patterns. This study aimed at establishing the impacts ofAfrican traditional environmental conservation practices among the Maasai people of Narok County, Kenya on environmental conservation. The study adopted a descriptive design. The target population was 215 community leaders from Maasai community in Narok County. Using stratified sampling technique, the study used a sample size of 132 respondents being 30% of the number of community leaders from Maasai community in Narok County. Primary data was collected using open ended and closed questionnaire. Quantitative data was analyzed by descriptive statistics. The findings indicated a significant decrease in Maasai traditional environmental conservation knowledge and education from the old to young Maasai elders. Knowledge of prohibitions on environmental factors such as demonization, declaration of taboos, age and gender restraints as well as use of totems was quite poor to Maasai elders below 45 years. The study indicated that the elder Maasai elders used various indigenous environmental norms in managing different elements of the biophysical environment with varying successes. The reduction in use of this knowledgewas confirmed by records of poor agricultural yields, loss of water sources, forest and vegetation covers and unpredictable weather and climate patterns over the last 40 years.The study concluded that traditional African practices aided in environmental conservation and should be incorporated in the Kenyan education curriculum.